Penerapan Pendekatan Saintifik Untuk Meningkatkan Hasil Belajar IPA - Riniwanti Hamang; Andi Makkasau (Universitas Negeri Makassar, 2024)
The problem of this research is motivated by the low learning outcomes of students in science. This is because the conventional learning process is more centered on the teacher. The formulation of the problem in this research is